2021
DOI: 10.3390/idr13040080
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects Following Administration of the First Dose of Oxford-AstraZeneca’s Covishield Vaccine in Bangladesh: A Cross-Sectional Study

Abstract: In response to the raging COVID-19 pandemic, Bangladesh started its vaccine administration in early 2021; however, due to the rapid development and launch of the vaccines in the market, many people had concerns regarding the safety of these vaccines. The purpose of this study was to evaluate the side effects that were experienced by the Bangladeshi residents after receiving the first dose of the Oxford-AstraZeneca’s Covishield vaccine (ChAdOx1nCoV-19). The study was conducted using both online and printed ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 20 publications
(26 reference statements)
7
19
1
Order By: Relevance
“…Also, comorbidities such as diabetes and hypertension topped the list. Our findings coincide with previous studies [ 7 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Also, comorbidities such as diabetes and hypertension topped the list. Our findings coincide with previous studies [ 7 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 94%
“…A survey conducted at Bangladesh found that below 10% (8.5%) of the participants were diagnosed with COVID-19 post-vaccination. Our data thus coincides with the study [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%